2008
DOI: 10.1017/s0952523808080619
|View full text |Cite
|
Sign up to set email alerts
|

A study of unusual Rayleigh matches in deutan deficiency

Abstract: This is the unspecified version of the paper.This version of the publication may differ from the final published version. Permanent repository link AbstractRayleigh match data were modeled with the aim of explaining the locations of match midpoints and matching ranges, both in normal trichromats and in subjects with congenital color deficiency. Model parameters included the wavelength of peak sensitivity of cone photopigments, the effective photopigment optical density, and the noise amplitude in the red-gree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 35 publications
1
41
0
1
Order By: Relevance
“…Such inconsistent findings make it difficult to quantify the subject's severity of color vision loss (21). The midpoint and the size of the matching range in anomaloscope matches, for example, are often used to screen for levels of deficiency, even when these parameters do not correlate well with the subject's loss of chromatic sensitivity (4,23). Previous studies also failed to show significant correlation between the number of errors subjects make on IT plates and the parameters of Nagel anomaloscope matches for both color vision deficient (6) and also for normal trichromats (15).…”
Section: Discussionmentioning
confidence: 90%
“…Such inconsistent findings make it difficult to quantify the subject's severity of color vision loss (21). The midpoint and the size of the matching range in anomaloscope matches, for example, are often used to screen for levels of deficiency, even when these parameters do not correlate well with the subject's loss of chromatic sensitivity (4,23). Previous studies also failed to show significant correlation between the number of errors subjects make on IT plates and the parameters of Nagel anomaloscope matches for both color vision deficient (6) and also for normal trichromats (15).…”
Section: Discussionmentioning
confidence: 90%
“…* Statistical analysis showed significant differences in chromatic thresholds between both age groups in deutan and tritan colour directions with static stimuli, and in all studied colour directions with dynamic test stimuli. ( Barbur et al, 2008). Linear regression functions between chromatic thresholds measured with computerised stimuli and the anomaloscope matching range indicated that slope did not significantly differ from 0, thereby confirming lack of correlation between anomaloscope matching range and chromatic thresholds measured along protan and deitan confusion lines (Table 5).…”
Section: Resultsmentioning
confidence: 51%
“…People's ability to distinguish wavelengths does degrade to about 6 nm at the ends of the spectrum where violet and red are located (Wright & Pitt, 1934), but recall that an nm is only one billionth of a meter. Of course, people with color deficient vision vary more in color perception tasks than those with normal color vision (Barbur, 2008), but only a small minority of the population (about 4%) have color deficiencies. Thus, while matching tasks do suggest disagreement, the disagreement is not nearly as much as naming tasks suggest and certainly not sufficient to support P-Disagreement.…”
Section: Discussionmentioning
confidence: 99%